Determinations of Asteroid Masses Using Mutual Encounters Observed in the Legacy Survey of Space and Time - Gary M. Bernstein; Negin Najafi; Daniel C. H. Gomes (The Planetary Science Journal)
Using published simulations of the 10 yr Legacy Survey of Space and Time (LSST), we forecast its ability to determine the masses of individual main-belt asteroids (MBAs) through precise astrometry of any pairs of the ≈1.2 million known MBAs undergoing close gravitational encounters during the survey. The uncertainty σ _I on the impulse applied to a tracer asteroid by its deflector is derived from the Fisher matrix of the tracer’s astrometric data, including an azimuthal acceleration from the Yarkovsky effect as a free parameter for each tracer. If only LSST observations are available, the mean forecasted σ _I is 7 × 10 ^−6 m s ^−1 for MBAs at apparent magnitude m _V  < 19.5, degrading ≈10× for m _V  = 23. The forecasted median uncertainty on the mass of a deflector MBA is ≈3 × 10 ^−14 M _⊙ , with a wide range of variation depending on the (random) configurations of the closest encounters. All of these figures improve ≈ fivefold if strong pre-LSST astrometry is available. Use of LSST data will increase the number of MBAs with masses measured to 20% accuracy or better from the present ≈70 to between 200 and 550, depending on quality of pre-LSST data, if all MBAs have mass-to-reflected-light ratios (M/Ls) at the low end of the currently measured bodies. If high-end M/Ls are more common, 580–1100 bodies will attain a signal-to-noise ratio > 5, including nearly all bodies with absolute magnitude H  < 10 and some as faint as H  = 13. We forecast that ≈20 new Jupiter Trojans could also have masses measured at <20% accuracy. Tables of the measurable deflector MBAs and their tracers are provided.